Die Situation der Kirchen in der Tschechoslowakei (1944-1948) - Smolík, Josef (Kirchliche Zeitgeschichte, 1989)
After the Second World War Roman Catholicism allied those political forces which defeated in 1948. In 1949 a statute decided that all activities of clergymen depended on the consent of the state which on his side guaranteed the sales of clergymen. - In the Evangelical Church of Bohemian Brothers most of the members accepted the new political situation. The most important representative of this church, J.H. Hromádka, a theological follower of Karl Barth, had already approached to socialism during the war. - The Lutheran Church which had overcome its traditional conservatism during the war, not had to be on its guard against nationalism. This temptation, however, did not get very dangerous owing to the new social circumstances. - The church revival was greatly supported by the ecumenical contacts taken up shortly after the end of the war.